Estimación de Corte Transversal de la Vulnerabilidad y la Pobreza Potencial de los Hogares en Nicaragua - Mauricio Gallardo Altamirano (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2009)
Siguiendo la metodología propuesta por Chaudhuri et al. (2002), en este trabajo se realiza una estimación de la vulnerabilidad de los hogares de Nicaragua usando datos de corte transversal. La vulnerabilidad de los hogares es evaluada como la probabilidad de que el valor esperado del logaritmo de su consumo, sea menor al logaritmo de cierto umbral de pobreza. Se consideran tanto las líneas de pobreza oficiales como las internacionales. La estimación del valor esperado y de la varianza del logaritmo del consumo se realiza por el típico procedimiento de Mínimos Cuadrados Generalizados Factibles en tres etapas, sugerido por Amemiya (1977). Los resultados validan la importancia de algunos determinantes de la vulnerabilidad que han sido estudiados para otros países. Al considerar que un hogar es potencialmente pobre, cuando su vulnerabilidad es mayor que 0.5, se encuentra que en Nicaragua las tasas de incidencia de la pobreza potencial son similares a las de la pobreza efectiva./ In this paper, using cross sectional data and following the methodology proposed by Chaudhuri et al. (2002), an estimation of household vulnerability to poverty in Nicaragua is made. The household vulnerability is assessed as the probability that the expected value of the logarithm of consumption is lower than the logarithm of certain threshold of poverty. Both official and International poverty lines are considered. The estimation of the expected value and the variance of the logarithm of consumption are made by typical three-step Feasible Generalized Least Squares procedure suggested by Amemiya (1977). The results validate the importance of some determinants of vulnerability that have been studied for other countries. Considering a household as potentially poor, when its vulnerability is more than 0.5, it is found that in Nicaragua the potential poverty headcounts ratios are similar to the effective poverty headcount ratios. – – In this paper, using cross sectional data and following the methodology proposed by Chaudhuri et al. (2002), an estimation of household vulnerability to poverty in Nicaragua is made. The household vulnerability is assessed as the probability that the expected value of the logarithm of consumption is lower than the logarithm of certain threshold of poverty. Both official and International poverty lines are considered. The estimation of the expected value and the variance of the logarithm of consumption are made by typical three-step Feasible Generalized Least Squares procedure suggested by Amemiya (1977). The results validate the importance of some determinants of vulnerability that have been studied for other countries. Considering a household as potentially poor, when its vulnerability is more than 0.5, it is found that in Nicaragua the potential poverty headcounts ratios are similar to the effective poverty headcount ratios.
Keywords: I32; 330; Armut; Nicaragua